Bridging the gap between research and practice: review of a targeted hospital inpatient fall prevention programme. Issue 6 (2nd December 2009) - Barker, A; Kamar, J; Morton, A; Berlowitz, D
Abstract : Objective: Falls among older inpatients are frequent and have negative consequences. In this study, the effectiveness of a fall prevention programme in reducing falls and fall injuries in an acute hospital was studied. Design: Retrospective audit. Setting: The Northern Hospital, an acute, metropolitan, hospital in Australia. Intervention: A multi-factorial fall prevention programme that included establishment of a multidisciplinary committee, risk assessment of all patients on "high-risk" wards and targeted interventions for patients identified as high risk. Main outcome measures: Fall and fall injury rates per 1000 occupied bed-days were analysed using generalised additive models (GAM) and, because of the presence of autocorrelation, generalised additive mixed models (GAMM), respectively. Results: During the 9-year observation of 271 095 patients, there were 2910 falls and 843 fall injuries. The GAM predicted rate of falls was stable in the 3 years after the programme was implemented, increased in 2006, then decreased between October 2006 and December 2007 from 4.13 (95% CI 3.65 to 4.67) to 2.83 (95% CI 2.24 to 3.59; p = 0.005). The GAMM predicted rate of fall injuries reduced from 1.66 (95% CI 1.24 to 2.21) to 0.61 (95% CI 0.43 to 0.88) after programme implementation (p<0.001). Conclusions: The falls rate varied throughout the observation period, and no significant change in the rate from preprogramme to postprogramme implementation was observed. The finding of no reduction in falls during the observation period may be explained by improved reporting throughout the observation period. The reduction in fall injuries was substantial and sustained. Identification of a local problem, use of a fall risk assessment to guide the delivery of simple interventions, integration of processes into daily clinical practice and creating systems that demand accountability of staff are factors that appear to have contributed to the programme's success.